Attainment of capital and competency towards intrinsic career success / Azizah Daut, Sany Sanuri Mohd Mokhtar and Faizuniah Pangil. - Daut, Azizah; Mohd Mokhtar, Sany Sanuri; Pangil, Faizuniah (Faculty of Business and Management and UiTM Press, Universiti Teknologi MARA, Shah Alam, Malaysia, 2014)
The main objective of Malaysia’s New Economic Model (NEM) outlines the need to produce quality human capital that commensurates with higher career success. As an ultimate reward, career success should be indicated by the tangible aspect as well as the personal conception of career success. This study specifically looks at the latter; on the link between capital and competencies gained during the attainment of MBA studies, to the intrinsic value of career satisfaction. As specified through educational attainment, human capital is defined by the scholastic, social, and cultural capitals whereas managerial competencies encompass the skills of knowledge, analytical, and general management. A total of 151 MBA graduates participated in the self-administered online survey and linear regression analysis was employed to test the relationships. The result reveals that among the three dimensions of human capital, cultural capital has the most positive significant association with career satisfaction. On the association between managerial competencies and career satisfaction, the skill of analytical is found to be a significant estimation of the intrinsic career success. The findings of this study are intended to contribute to a better understanding of assessing the intrinsic value of career success. It presents a means for the higher-education providers and policy makers to devise a strategy that generates a balanced human capital in terms of their extrinsic and intrinsic career success.